Leveraging AI and Generative AI for Medical Device Innovation: Enhancing Custom Product Development and Patient Specific Solutions - Nuka, Sai Teja (Journal of Neonatal Surgery, 2025)
The integration of artificial intelligence (AI) into CAD platforms will dramatically influence the way medical devices are designed, produced, and evaluated. It will allow the creation of intelligent customization platforms for perfect natural device design, dealing with patient-specific compatibility, function, and intraoperative customization. Similar trends occurred for 3D printing and have led to the democratization of an exciting innovation. AI tools are essential to facilitate the design’s performance evaluation of these complex 4D concepts, made of a new generation of advanced soft active materials, actuators, and novel bioprinting strategies. Advanced machine learning will be used to improve predictive generative platforms' biomechanical bio-operation and bio-integration simulation, leading to the design of a novel generation of temporary sophisticated 4D custom-printed objects. Examples of these new advanced bioprinted smart active materials’ future patient-specific applications will be given for drug-printed biodegradable temporary medical devices, passively adaptive volumetric intravascular devices, and internally actuated endovascular complex were driven objects. AI transforming medical practices, doctors, health providers, or hospitals were where patients head to receive various treatments. AI is in the process of becoming omnipresent, perceiving the patient’s symptoms and medical history and providing a proper diagnosis. In the long run, this may lead to a paradigm shift where instead of reaching out to the medical devices, the medical devices will be sent to the necessary places where the patients/people live, study, work, and relax. Therefore, increasing attention is placed on wearable or ubiquitous medical technologies exploiting generative AI tools, providing the shift from passive monitoring to active patient custom home care. Examples of how generative AI fueled the new medical devices from their idea generation and development to the next real-world applications are given as easily customizable ultrathin epidermal sensory patch, pocket essential skin care devices, and customized comfort shoe inserts.